CULTIVATION OF HENNA WATER PLANTS AS AN ECONOMIC VALUE COMMODITY IN GETAKAN VILLAGE, KLUNGKUNG REGENCY - Lestara Permana, Gusi Putu; Sastra Dewanti, Wayan Ari; Wirya Darma, I Made; Wahyudi Oktavia Gama, Adie; Suparna, Putu; Adhiya Garini Putri, Dewa Ayu; Kalfika Anggria Wardani, Kadek Devi; Sutama, I Wayan (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2023)
The farming program in the village is 70% dependent on rice and cloves. which has approximately a harvest time interval of three to one year, while the percentage of girlfriend water flowers (Impatiens balsamina) cultivation in the village of Getakan is still 30%, therefore activities are more focused on raising the cultivation of water henna plants, so that farmers have additional income every day. However, currently there are problems, in terms of reduced flower production, lack of pest management using pesticides, minimal flower quality improvement, lack of knowledge about social media as a means of promotion, and stages of online education. This study aims to provide education regarding steps, tips, and also information related to the application of girlfriend water flowers (Impatiens balsamina) cultivation and promotion on social media as well as increasing knowledge and also developing community farming related to optimizing the potential of paddy fields by cultivating commodities that can be used to produce and make a product as additional income for rural communities. The results obtained by the people of Getakan Village can produce good and quality girlfriend water flowers (Impatiens balsamina) so that they increase their daily income.